Wheat lines exhibiting variation in tolerance of Septoria tritici blotch differentiated by grain source limitation - Collin, F.; Bancal, P.; Spink, J.; Kock Appelgren, P.; Smith, J.; Paveley, N.D.; Bancal, M.O.; Foulkes, M.J. (Elsevier, 2018)
Septoria tritici blotch (STB) is the most damaging disease of wheat crops in Europe. Because of the partial nature of genotypic resistance or the increasing resistance against fungicides, the tolerance, i.e. maintaining yield in the presence of expressed disease, is a relevant alternative. Tolerance is generally estimated through the yield loss per unit of source reduction, contrasts of tolerance between genotypes have been observed previously suggesting that either increasing the source availability or improving the use of stored assimilate could improve tolerance. This paper aims at developing a source/sink approach to understand the tolerance mechanism and identifying potential traits to increase tolerance of STB. A field experiment was designed to explore the relation between tolerance of STB and source/sink balance. Based on six wheat genotypes contrasting for tolerance exposed to natural STB epidemics, late nitrogen fertilization and a 50% spikelet removal were applied to change the source/sink balance. The tolerance of genotypes was quantitatively estimated over three additional field experiments. We found that STB tolerance was correlated with traits of healthy crops (high individual grain weight and high green leaf lamina area as the proportion of leaf 3). The spikelet removal revealed a highly variable degree of source limitation for grain filling amongst the six genotypes. Thus, we proposed an easily calculated index that highly correlated positively with the labor intensive estimation of STB tolerance. Finally, potential yield and tolerance were not correlated, which suggests that breeding for yield performance and tolerance could be possible.